(untitled) (American Journal of Islam and Society, 2006)
Originally intended as a short textbook codifying the existing knowledge of Islamic political thought, Patricia Crone’s God’s Rule developed into a fuller and more comprehensive examination of the first six centuries of government and Islam. Crone, perhaps better known for her more controversial works, such as Hagarism (Cambridge: 1977), God’s Caliph (Cambridge: 1986), and Meccan Trade and the Rise of Islam (Oxford: 1987), is no stranger to Islamic political theory, having written Slaves on Horses: The Evolution of the Islamic Polity (Cambridge: 1980). In her present book, the reader will find an accessible, readable, and scholarly contribution that is largely devoid of controversy while retaining a healthy skepticism of the sources, as one would expect from an historian. Primarily written for the non-specialist, the intention is to render the contextual theory, practice, and development of political thought during the early centuries of Islam (c. 622-1258) intelligible to the general reader. Divided into four sections, Crone seeks to cover the broader trends and themes in the transition from the Prophet’s polity to that of the Buyids and the Seljuqs. Along the way, she guides the reader through the complex web of Islamic history, starting, in part 1, with the basic Muslim conceptual understanding of government and state up to the first civil war, sect formation, and the Umayyad period. Here, the central importance was the leader, as successor to the Prophet, who weds truth and power and thereby rightly guides the Muslim community by providing legal legitimacy and a moral example. The question of legitimacy came to the fore during the first civil war, which resulted in the formation of various sects and the rise of the Umayyad dynasty ...